O estudo piloto dos impactos antrópicos do Rio Pará e Rio Tracuateua na Região Metropolitana de Belém-Pa (Brasil) - MORAES, Laura Beatriz da Silva (2023)
The pilot research had as main objective recognise and discuss the geosocioenvironmental realities with emphasis in the quality of the water of Pará River in the stretch of Furo das Marinhas and Tracuateua River in the metropolitan region of Belém. Field research was made, with exploratory traits, as part of the technical scientifical contents of the discipline Introduction to the Environmental Science from in Chemistry course in the Campus of Ananideua from the Federal University of Pará. It was examined in locu the conditions of water in those rivers, from Where quantiqualitative physiochemical samples were collected and analysed to identify the quality of water in part of the hydrographic basin. The analysis were determined following the procedures conceded by Guedes (2023). Through this, it was understood the challenges faced, with proposal of solutions to promote and preserve de hydrical resources. As conclusion, it is observed the presence of detritus and sewage on the stretches of Pará River, causing impacts on health and environment, needing public policies of garbage collection and selective garbage collection, as well as Investments on environmental education.